How to Deal With Seafloor Marine Litter: An Overview of the State-of-the-Art and Future Perspectives - Madricardo, Fantina; Ghezzo, Michol; Nesto, Nicoletta; Mc Kiver, William Joseph; Faussone, Gian Claudio; Fiorin, Riccardo; Riccato, Federico; Mackelworth, Peter Charles; Basta, Jelena; De Pascalis, Francesca; Kruss, Aleksandra; Petrizzo, Antonio; et al. (Frontiers in Marine Science, 2020)
Marine litter is a significant and growing pollutant in the oceans. In recent years, the number of studies and initiatives trying to assess and tackle the global threat of marine litter has grown exponentially. Most of these studies, when considering macro-litter, focus on floating or stranded litter, whereas there is less information available about marine litter on the seabed. The aim of this article is to give an overview of the current state-of-the-art methods to address the issue of seafloor macro-litter pollution. The overview includes the following topics: the monitoring of macro-litter on the seafloor, the identification of possible litter accumulation hot spots on the seafloor through numerical models, and seafloor litter management approaches (from removal protocols to recycling processes). The article briefly analyzes the different approaches to involve stakeholders, since the marine litter topic is strongly related to the societal engagement. Finally, attempting to answer to all the critical aspects highlighted in the overview, the article highlights the need of innovative multi-level solutions to induce a change toward sustainable practices, transforming a problem into a real circular economy opportunity.